Drug Seeking and Relapse: New Evidence of a Role for Orexin and Dynorphin Co-transmission in the Paraventricular Nucleus of the Thalamus - Matzeu, Alessandra; Martin-Fardon, Rémi (Frontiers in Neurology, 2018)
The long-lasting vulnerability to relapse remains the main challenge for the successful treatment of drug addiction. The core neurocircuitry that participates in the regulation of drug-seeking behavior has been well described and includes the ventral tegmental area (VTA), central nucleus of the amygdala, bed nucleus of the stria terminalis, nucleus accumbens, basolateral amygdala, hippocampus, and medial prefrontal cortex. The orexin (hypocretin) system is known to participate in the regulation of a range of physiological processes (e.g., feeding, energy metabolism, and arousal), and is also recruited by drugs of abuse. Orexin (Orx) neurons are located in the lateral hypothalamus (LH) and play an important role in drug addiction. Accumulating evidence indicates that the paraventricular nucleus of the thalamus (PVT), which receives major Orx projections from the LH, is an integral part of the circuitry that controls drug-seeking behavior. All Orx neurons contain dynorphin (Dyn), and Orx and Dyn are co-released. In the VTA, they play opposing roles in reward and motivation. To fully understand the physiological and behavioral roles of Orx transmission in the PVT, it is critical to consider that Orx neurons that project to the PVT may co-release Orx with another peptide, such as Dyn. The PVT expresses both Orx receptors (OrxRs) and opioid receptors (KORs), suggesting that Orx and Dyn act in tandem when released in the PVT, in addition to the VTA. The present review discusses recent findings that suggest the maladaptive recruitment of Orx/Dyn-PVT neurotransmission by drugs of abuse.